Nepal’s Economic Diplomacy: An Analytical View - Timalsina, Saroj Kumar; Karki, Jantraj (The Journal of Economic Concerns, 2025)
The economic diplomacy approach of Nepal has been critically analyzed purposefully in this article specifically in relation to its role towards strengthening strong trade, development, and national security. Systematic literature reviews were conducted and data were gathered through desk research, keyword and e-resources searching, online interviews, YouTube analysis, and archival documents. Foreign policy is revealed to be influenced extensively by trade and development is strongly related to trade and security agendas. It emphasizes that economic diplomacy must respond to inclusive, sustainable, and long-term development. Additionally, the early expansion of global trade left enormous implications on the development trajectory of Nepal, and therefore there have been policy reforms in order to stimulate trade. It reiterates that foreign aid, FDI, and hard and soft loans are needed to enhance Nepal’s economy. The paper concludes by presenting strategic recommendations that attempt to fill existing policy vacuums and optimize the efficacy of Nepal’s economic diplomacy.